The Implementation of Textual Coherence on the Albanian Subtitles of “Great Gatsby” Film - Vula, Elsa (European Journal of Multidisciplinary Studies, 2018)
Coherence as one of the most significant elements of text analysis will be the main focus of this research paper. Based upon relevant theoretical background it presents empirical study of coherence in Albanian subtitles of “Great Gatsby” film. This paper will elaborate on the theory of coherence focusing on its role and importance in the text, as well as the difficulties of implementing it during the translation process. The empirical research has been realized on the analysis of fourteen Albanian subtitles from the “Great Gatsby” film, furthermore the study based on the translation (Albanian subtitles) elaborates the implementation of coherence and changes that are made during the translation process. In addition, there are identified the problems, structural changes, cultural loss, parts of the film that were not translated, and at the same time recommendations are given for each selected Albanian subtitle.